Isolation, identification and characterisation of antibacterial compounds from Carissa lancelota R.Br.Root - Hettiarachchi, Dhanushka Sugeeshwara (Curtin University, 2006)
Carissa lanceolata (conkerberry) is a perennial woody shrub used in traditional medicine by indigenous communities in Western Australia, the Northern Territory and Queensland for various medical conditions such as toothache, respiratory infections and the cleaning of sores, which all strongly indicate an antibacterial activity. A literature review revealed that the wood of this plant possesses significant antibacterial activity, which was found to be related to the presence of eudesmane type sesquiterpenes. C. edulis and C. carandus are frequently used in other traditional systems of medicine in different parts of the world, and thus have also been investigated for bioactive compounds and pharmacological properties. Some of these were found to be in line with the main findings of this work. Carissa lanceolata root was shown to exhibit significant antibacterial activity against both Gram negative and Gram positive organisms. A micro-broth dilution assay was performed on 96-well plates using resazurin as an indicator for microbial growth of Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis and Staphylococcus aureus. Bioassays carried out in this work showed that crude extracts of root bark and wood, particularly their polar constituents were more active against the four strains of bacteria tested.Chemical investigation of the root bark revealed that it contains a volatile oil, which was isolated by steam distillation as well as solid phase micro extraction. It was found to consist of a single compound, which was identified as 2'-hydroxy acetophenone. The identity of this compound was confirmed by GC/MS and 1H NMR spectroscopy. Furthermore, the eudesmane-type sesquiterpene, carissone, was isolated from the root bark DCM and root wood hexane extracts. Its chemical identity was confirmed by IR, 1 [superscript] H and 13 [superscript] C NMR spectroscopy. The lignan, carinol, on the other hand, was isolated from the moderately polar fractions of the root wood MeOH extract. The obtained IR and 1 [superscript] H NMR data as well as Rf values all correspond to the literature. Two other yet unidentified compounds were isolated, but further studies into their chemistry and antibacterial activity were not possible in this current study. The antibacterial activity of the isolated compounds was considerable, with 2'-hydroxy acetophenone exhibiting the strongest effect, followed by carinol and then carissone.